1991
DOI: 10.1111/j.1471-4159.1991.tb02033.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Inositol 1,4,5‐Trisphosphate and Inositol 1,3,4,5‐Tetrakisphosphate Mass Accumulations in Cultured Adrenal Chromaffin Cells in Response to Bradykinin and Histamine

Abstract: In previous studies it has been shown that both bradykinin and histamine increase the formation of 3H-labeled inositol phosphates in adrenal chromaffin cells prelabelled with [3H]inositol and that both these agonists stimulate release of catecholamines by a mechanism dependent on extracellular calcium. Here, we have used mass assays of inositol 1,4,5-trisphosphate [Ins(1,4,5)P3] and inositol 1,3,4,5-tetrakisphosphate [Ins(1,3,4,5)P4] to investigate changes in levels of these two candidates as second messengers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…These include muscarinic cholinoceptors (Cheek & Burgoyne, 1985), opioid peptide (Lemaire et al, 1981), substance P (Livett et al, 1979), bradykinin (Owen et al, 1989), histamine HI (Chaliss et al, 1991), dopamine DI and D2 (Stauderman & Pruss, 1990;Huettl et al, 1991), prostaglandin E2 (Negishi et al, 1989;Ito et al, 1991), adenosine (Chern et al, 1988), angiotensin II (Marley et al, 1989;O'Sullivan & Burgoyne, 1989) and GABAA receptors (Castro et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…These include muscarinic cholinoceptors (Cheek & Burgoyne, 1985), opioid peptide (Lemaire et al, 1981), substance P (Livett et al, 1979), bradykinin (Owen et al, 1989), histamine HI (Chaliss et al, 1991), dopamine DI and D2 (Stauderman & Pruss, 1990;Huettl et al, 1991), prostaglandin E2 (Negishi et al, 1989;Ito et al, 1991), adenosine (Chern et al, 1988), angiotensin II (Marley et al, 1989;O'Sullivan & Burgoyne, 1989) and GABAA receptors (Castro et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In supporting this finding, it has been shown that cyclopiazonic acid easily penetrates into the cytoplasm through the plasma membrane and reduces Ca 2+ -ATPase activity in sarcoplasmic/endoplasmic reticulum, resulting in increase in the subsequent Ca 2+ release from those storage sites and thereby increase of Ca 2+ -dependent K + -current [38]. Moreover, in bovine adrenal chromaffin cells, stimulation of muscarinic ACh receptors is also proposed to cause activation of phosphoinositide metabolism, resulting in the formation of inositol 1,4,5-trisphosphate, which induces the mobilization of Ca 2+ from the intracellular pools [35,39]. However, in the present study, it is uncertain whether the inhibitory effect of the olmesartan on Ca 2+ movement from intracellular pools is due to their direct effect on the PI response or the indirect effect as a result of AT1 receptor blockade by olmesartan.…”
Section: Discussionmentioning
confidence: 99%
“…In supporting this finding, it has been shown that cyclopiazonic acid easily penetrates into the cytoplasm through the plasma membrane and reduces Ca 2+ -ATPase activity in sarcoplasmic/endoplasmic reticulum, resulting in increase in the subsequent Ca 2+ release from those storage sites and thereby increase of Ca 2+ -dependent K + -current (Suzuki et al, 1992). Moreover, in bovine adrenal chromaffin cells, stimulation of muscarinic ACh receptors is also proposed to cause activation of phosphoinositide metabolism, resulting in the formation of inositol 1,4,5-trisphosphate, which induces the mobilization of Ca 2+ from the intracellular pools (Cheek et al, 1989;Challiss et al, 1991). However, in the present study, it is uncertain whether the inhibitory effect of the losartan on Ca 2+ movement from intracellular pools is due to their direct effect on the PI response or the indirect effect as a result of AT1 receptor blockade by losartan.…”
Section: Discussionmentioning
confidence: 99%